The impact of XR applications’ user experience-based design innovativeness on loyalty - Joo-Eon Jeon (Cogent Business & Management)
Web-based extended reality (XR) is an umbrella term for applications such as augmented reality and virtual reality. However, prior studies have only focused on the technological advancement of XR applications. Thus, this research explored the impact of the user experience-based design innovativeness (UXBDI) of XR applications, which refers to the novelties in the design of an existing application created to satisfy user loyalty. This research proposed and examined how XR applications’ UXBDI affect user engagement and loyalty and used structural equation modeling to test the impact of UXBDI on web-based XR application loyalty. A total of 332 users of XR applications participated in the online questionnaire. The findings revealed that attractiveness and interaction, as sub-dimensions of UXBDI, increased XR application engagement. Moreover, an indirect effect of usability on loyalty indicated that engagement acts as a mediator. This study demonstrates that XR applications’ UXBDI is a key component for the user-XR application relationship. These results are meaningful in guiding the management of the XR application cycle.